Pragmatic Inquiry and Religious Communities Charles Peirce, Signs, and Inhabited Experiments - Daniel-Hughes, Brandon (Springer International Publishing, 2018)
This book examines the ways in which religious communities experimentally engage the world and function as fallible inquisitive agents, despite frequent protests to the contrary. Using the philosophy of inquiry and semiotics of Charles Sanders Peirce, it develops unique naturalist conceptions of religious meaning and ultimate orientation while also arguing for a reappraisal of the ways in which the world's venerable religious traditions enable novel forms of communal inquiry into what Peirce termed "vital matters." Pragmatic inquiry, it argues, is a ubiquitous and continuous phenomenon. Thus, religious participation, though cautiously conservative in many ways, is best understood as a variety of inhabited experimentation. Religious communities embody historically mediated hypotheses about how best to engage the world and curate networks of semiotic resources for rendering those engagements meaningful. Religions best fulfill their inquisitive function when they both deploy and reform their sign systems as they learn better to engage reality.